2015
DOI: 10.1159/000381510
|View full text |Cite
|
Sign up to set email alerts
|

Mitophagy: Basic Mechanism and Potential Role in Kidney Diseases

Abstract: Background: Mitochondria play fundamental roles in cellular metabolism, signaling, and viability. Disruption of mitochondria not only leads to dysfunction of the organelles but also activates mechanisms of cell injury and death, contributing to the pathogenesis of various diseases. Summary: Removal of damaged mitochondria is therefore crucial for cellular homeostasis and survival. Mitophagy, the selective elimination of mitochondria via autophagy, is an important mechanism of mitochondrial quality control in p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 101 publications
1
31
0
Order By: Relevance
“…35 Despite these observations, the main pathway of mitophagy that is responsible for mitochondrial quality control in kidneys remains unclear and the role of mitophagy in the pathogenesis of renal diseases remains to be elucidated. 36 In the present study, we have demonstrated mitophagy induction in proximal tubular cells during renal I-R, which is suppressed in Pink1-and Park2-deficient mice. Notably, Pink1 and Park2 deficiency aggravate renal I-Rinduced kidney injury, and enhance mitochondrial damage, ROS production, tubular cell apoptosis and tubulointerstitial inflammation.…”
Section: Introductionsupporting
confidence: 58%
“…35 Despite these observations, the main pathway of mitophagy that is responsible for mitochondrial quality control in kidneys remains unclear and the role of mitophagy in the pathogenesis of renal diseases remains to be elucidated. 36 In the present study, we have demonstrated mitophagy induction in proximal tubular cells during renal I-R, which is suppressed in Pink1-and Park2-deficient mice. Notably, Pink1 and Park2 deficiency aggravate renal I-Rinduced kidney injury, and enhance mitochondrial damage, ROS production, tubular cell apoptosis and tubulointerstitial inflammation.…”
Section: Introductionsupporting
confidence: 58%
“…BNIP3 and NIX are also apoptotic regulators that can induce cell death or autophagy by increasing the production of ROS, by binding to pro-apoptotic proteins of the BCL-2 family, or by inhibiting the GTP-binding protein RHEB, an upstream activator of mTOR 131–133 . Previous studies suggest that crosstalk exists between both of the mechanisms that can regulate mitophagy 127,134,135 , although the mechanisms of this proposed crosstalk are unclear and additional studies are needed to determine the mechanisms that regulate mitophagy in renal disease.…”
Section: Maintaining Mitochondrial Homeostasismentioning
confidence: 99%
“…Proper mitophagy is not only a prerequisite for cell survival but also plays a crucial role under pathological pressures, including hepatic diseases, angiocardiopathy, and neurodegeneration (Dai et al, 2010;Lionaki, Markaki, Palikaras, & Tavernarakis, 2015;Tang, He, Liu, & Dong, 2015). Mitophagy can be both beneficial and harmful under certain pathophysiological conditions (Palikaras, Daskalaki, Markaki, & Tavernarakis, 2017).…”
mentioning
confidence: 99%